The pharmaceutical applications of total flavonoids extract from Isatis tinctoria L. leaves - Jingyi Xu; Zhiwei Lan; Shuqi Wang; Yueting Guo; Jing Ning; Yang Song; Mingchun Liu; Chunlian Tian (Elsevier, 2022)
Isatis tinctoria L. leaves (Folium isatidis), as dried leave of the isatis indigotica in the cruciferous family, has a variety of pharmacological effects, including regulation of immune function, anti-inflammatory, bacteriostasis, antipyretic effect. In this study, total flavonoids extract from Folium isatidis was systematically studied about extractive process, main components, antibacterial, antioxidant and anti-inflammatory activities. The total flavonoids extract yield was (7.65±0.07)% under the optimal extraction parameters of ethanol concentration 54.37%, ratio of solvent volume to material weight 40:1 ml/g, and ultrasonic extraction time 20 min. Nineteen chemical components were inferred and identified by UPLC-QTOF-MS method. Although the extract showed mild antibacterial and antioxidant effects with MIC values 31.25, 62.5, 125 and 125 mg/ml against Streptococcus, Salmonella, Staphylococcus aureus and Escherichia coli, and IC50 DPPH 12.64 µg/ml, IC50 ABTS 16.72 µg/ml and FRAP value at 0.11 mmol Fe2+/100 µg/ml compared with the positive control butylated hydroxytoluene with IC50 DPPH 8.13 µg/ml, IC50 ABTS 2.22 µg/ml and FRAP value at 0.16 mmol Fe2+/100 µg/ml. It exhibited better anti-inflammatory effects in LPS induced RAW 264.7 cell (50, 100 and 200 µg/ml of TFE) and ALI mice (100, 250, or 500 mg/kg•b•w of TFE), which was demonstrated by reducing cell phagocytic activity, decreasing the content of pro-inflammatory cytokine and inflammatory mediator, and improving lung tissue injury. Furthermore, the mechanism of anti-inflammatory action was further revealed to be related to the regulation of TLR4-TRIF-NF-κB signaling pathway. These studies revealed that total flavonoids extract could be used as a natural and green candidate for anti-inflammatory drugs and enrich the variety of clinical anti-inflammatory drugs.